A Literature Survey on Plant Grafting Technology and Internet of Things Solutions - Nurhalim, Rifqy; Nuha, Hilal H. (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Hundreds of works have been reported related to the agricultural technology. This paper can be regarded as an initial effort to summarize great works performed by researcher and scientists. First, we provide the works on the effect of rootstock choices. Second, the budding factor is presented by summarizing the works on the field. Finally, the success rate and feasibility of each technique is presented